Environmental Stress and Aroma Production During Wine Fermentation - Fairbairn, S.C.; Smit, A.Y.; Jacobson, D.; Prior, B.A.; Bauer, F.F. (South African Journal of Enology and Viticulture, 2016)
The sensory description of wine uses the widest range of descriptive terminology of all food products, reflecting the complex nature of a product whose character depends on the balance of hundreds of individual flavour-active compounds. There are many tools that can influence flavour profiles or wine styles, one of which is the choice of a specific yeast strain. Yeasts contribute to wine flavour by producing volatile metabolites with different flavour profiles. The impact of changing environmental conditions on the production of flavour compounds by yeast strains remains largely unexplored. This is the first study investigating the impact of two mild fermentation stresses, hyperosmotic and temperature stress, on aroma production in synthetic must by commercial Saccharomyces cerevisiae wine strains. Hyperosmotic stress was imposed by cultivation of the yeast for 21 days in the must containing either 0.3 or 0.5 M sorbitol. The transient temperature stresses were applied for 16 h at 8° or 37°C for either two or eight days after commencement of the fermentation. Greater glycerol and acetic acid levels were produced by most yeasts when only hyperosmotic stress was applied. Hyperosmotic and temperature stress conditions produced a limited number of significant changes to the profile of the esters, higher alcohols and volatile fatty acids. These changes differed significantly for each strain and stress treatment, suggesting that the fermentation conditions can significantly alter the aromatic profile of a wine, although these stress impacts cannot be predicted in general. The changes to the aromatic profile are specific to each individual wine yeast strain.